Study guides

Q: Solve 2a plus 3 equals 11?

Write your answer...

Submit

Related questions

depends what 'a' =

a + a + a - 2a = 3a - 2a = a

Subtract 2a from each side: P - 2a = b ie b = P - 2a

If: 2a+13 = 5a+1 Then: a = 4

Solve the following equation for A : 2A/3 = 8 + 4A

the answer

-2a + 5 = 1 -2a = -5 + 1 -2a = -4 a = -4/-2 a = 2

1

2a+5a+9a = 16a

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)

:a = .5(hb+c) :2a = hb+c :2a−c = hb :(2a−c)/h = b

5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9

a+a=1 2a=1 a=1/2

It is the expression 3 + 2a.

3a x 2a =24

A equals 20.

(2a + 1)(4a2 - 2a + 1)

A=2

2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.

2a + 2b = 160 But b = a + 40 so 2a + 2(a + 40) = 160 ie 2a + 2a + 80 = 160 or 4a = 80 ie a = 20 Then b = a + 40 gives b = 20 + 40 = 60 Solution: a = 20, b = 60

b = 2a + 11a + b = 5 which is b = 5 - atherefore2a + 11 = 5 - a (which is b = b)2a + a = - 11 + 53a = - 6a = - 2looking at first equation substitute - 2 for a:b = 2a + 11b = 2*(- 2) + 11b = - 4 +11b = 7to check:a + b = 5- 2 + 7 = 5

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

a = 1

A = h/2*(a + b) So 2A/h = a + b and therefore, a = 2A/h - b

2a + 3a + 4 = 5a + 4